Electrophysiologic Analysis of Tight Junction Size and Charge Selectivity. Issue 6 (9th June 2021) - Shashikanth, Nitesh; Rizzo, Heather E.; Pongkorpsakol, Pawin; Heneghan, John F.; Turner, Jerrold R.
Abstract: Tight junctions form selectively permeable barriers that limit paracellular flux across epithelial‐lined surfaces. Rather than being absolute barriers, tight junctions in many tissues allow ions, water, and other small molecules to cross on the basis of size and charge selectivity via the high‐capacity pore pathway. Most probes currently used to assess tight junction permeability exceed the maximum size capacity of the pore pathway. As a result, available analytical tools have generally been limited to measurement of transepithelial electrical resistances. These provide no information regarding size selectivity and, therefore, cannot be used to distinguish between the pore pathway and the leak pathway, a low‐capacity route that accommodates larger macromolecules. This article describes use of dilution potential and bi‐ionic potential measurements for analysis of tight junction size and charge selectivity within monolayers of cultured epithelial cells. © 2021 Wiley Periodicals LLC. This article was corrected on 25 August 2021. See the end of the full text for details. Basic Protocol 1 : Culture of MDCK monolayers on semipermeable supports and induction of claudin‐2 expression Basic Protocol 2 : Configuring voltage/current clamp and other equipment Basic Protocol 3 : Measuring dilution and bi‐ionic potentials Basic Protocol 4 : Calculating ion permeabilities and pore diameter Support Protocol : Preparation of agar bridges and electrophysiology rig setup